2022
DOI: 10.1021/acsami.1c23381
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Modulated Lattice-Polarity-Controlled Epitaxy of III-Nitride Heterostructures on Si(111)

Abstract: Monolithic integration of wurtzite III-nitrides with nonpolar silicon (Si), the two most-produced semiconductor materials, is essential and critical for a broad range of applications in electronics, optoelectronics, quantum photonics, and renewable energy. To date, however, it has remained challenging to achieve III-nitride heterostructures on Si with controlled lattice-polarity. Herein, we show that such critical challenges of III-nitrides on Si can be fundamentally addressed through a unique interfacial modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…It is well known that in the ABF-STEM image, the darkest spots correspond to the heaviest atoms. [65,66] Therefore, we are able to configure the atomic stacking sequence of Al and N atoms, which is embedded in the ABF-STEM image (Figure 2c). Comparing with the atomic structure of wurtzite AlN, we confirmed that the lattice-polarity of the transferred AlN membrane is N-polar.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that in the ABF-STEM image, the darkest spots correspond to the heaviest atoms. [65,66] Therefore, we are able to configure the atomic stacking sequence of Al and N atoms, which is embedded in the ABF-STEM image (Figure 2c). Comparing with the atomic structure of wurtzite AlN, we confirmed that the lattice-polarity of the transferred AlN membrane is N-polar.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the high dislocation density within the GaN epilayer, the majority (>85%) of the nanowires feature nearly perfect crystallinity, indicating a filtering effect of the nanowire structure on propagating dislocations 40 . The threading dislocation density (TDD) within the GaN film is measured to be ~3 × 10 10 cm −2 41 . The TDs are observed to terminate on the sidewall of the nanowires, as shown in the cross-sectional scanning transmission electron microscopy (STEM) image (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At the AlN growth temperature of 980 °C, there could be a high Si concentration in the Al−Si eutectic. 38 As a consequence, the incorporation of Si atoms during the subsequent AlN growth results in an Al-Si-N interlayer formation, 44 which severely deteriorates the crystalline quality of the AlN layer. In contrast, the USAP conditions actually create a very weak supersaturated environment and prevent the formation of Al droplets and thus the Al−Si alloying during the TMAl pretreatment.…”
Section: Resultsmentioning
confidence: 99%